Game optimization scheduling of virtual power plant considering electricity， carbon and green certificate markets - LI Jian; ZHANG Zhengjie; DU Long; FAN Bei; WANG Yuanhao; ZHOU Xia (Zhejiang dianli)
With the integration of a large number of distributed energy resources participating in the electricity， carbon， and green certificate trading markets through the form of virtual power plants （VPPs）， the coordinated optimization dispatch among multiple VPPs in these joint markets has garnered significant attention. As a result， a joint operation mechanism across multiple markets has been studied， and a joint trading framework for electricity， carbon， and green certificate markets has been designed. An optimal dispatch model based on dynamic evolutionary game theory has been proposed for multiple VPPs. By constructing practical examples， the simulation of cooperative evolution strategy and coordinated dispatch among multiple VPPs is performed， and the changing cooperative patterns of VPPs under different carbon allowances are compared. The simulation results validate the efficacy of the proposed model. The proposed strategy manages to balance the competing interests among VPPs， thereby enhancing their participation and enthusiasm in market trading.